Strategi Komunikasi Melalui Media Visual Penyuluh Agama Hindu Pada Masa Pandemi Covid-19 di Kota Mataram - Ni Nyoman Harnika (Universitas Bumigora, 2020)
The Covid-19 pandemic has a large influence on the social interactions of Hindu religious counselors to communicating Hindus religious teachings. This is due to government policies that apply social distancing or keep a distance of one to two meters, and do not involve large numbers of people who can cause crowds. This policy has led to changes in the social interaction of a Hindu religious counselor in carrying out his duties as an instructor in communicating Hindu